A rare case of choroidal metastasis presented after conservative management of endometrial cancer. Issue 6 (1st October 2006) - Cormio, G.; Martino, R.; Loizzi, V.; Resta, L.; Selvaggi, L.
Abstract : Hematogenous dissemination from endometrial cancer is quite rare. We report a 31-year-old woman who developed choroidal metastasis following conservative management of early-stage endometrial carcinoma. She had received kidney transplantation and was taking steroids and cyclosporine. Three years after hysterectomy for persistent endometrial carcinoma, she developed multiple metastatic disease (to both lungs and right pelvis), and while on treatment with paclitaxel and carboplatin, she complained of a rapid visual deterioration. Ophthalmologic evaluation revealed a metastatic choroidal tumor associated with multiple central nervous system metastases. The patient refused further treatment and died 1 month after diagnosis of choroidal involvement. In conclusion, this is the first reported case of choroidal metastasis from endometrial cancer and highlights the need to consider immunosuppressive treatment as an absolute contraindication to conservative fertility-sparing treatment in gynecological malignancies.